The Response of Smokers to Health Warnings on Packs in the United Kingdom and Norway Following the Introduction of Standardized Packaging. Issue 9 (18th February 2021) - Moodie, Crawford; Best, Catherine; Lund, Ingeborg; Scheffels, Janne; Critchlow, Nathan; Stead, Martine; McNeill, Ann; Hitchman, Sara; Mackintosh, Anne Marie
Abstract: Introduction: Standardized packaging was phased in between May 2016 and May 2017 in the United Kingdom and July 2017 and July 2018 in Norway. In both countries, the health warnings on packs prior to standardized packaging being implemented were from the former Tobacco Products Directive library of warnings (text warnings covering 43% of the pack front and pictorial warnings covering 53% of the pack reverse). The warnings on packs, postimplementation, were from the current Tobacco Products Directive library of warnings (novel pictorial warnings covering 65% of the pack front and reverse) for the United Kingdom but unchanged in Norway. Aims and Methods: Longitudinal online surveys were conducted prior to standardized packaging (United Kingdom: April–May 2016; Norway: May–June 2017) and postimplementation (United Kingdom: September–November 2017 and May–July 2019; Norway: August–September 2018). We explored smokers' response to the on-pack warnings (salience, cognitive reactions, and behavioral reactions). Results: In the United Kingdom, noticing warnings on packs, reading or looking closely at them, thinking about them, thinking about the health risks, avoidant behaviors, forgoing cigarettes, and being more likely to quit due to the warnings significantly increased from waves 1 to 2, and then decreased from waves 2 to 3, but remained higher than at wave 1. In Norway, noticing warnings, reading or looking closely at them, thinking about them, thinking about the health risks, and being more likely to quit due to the warnings significantly decreased from waves 1 to 2; avoidant behaviors and forgoing cigarettes remained unchanged. Conclusions: The inclusion of large novel pictorial warnings on standardized packs increases warning salience and effectiveness. Implications: Two longitudinal online surveys in the United Kingdom and Norway explored the impact of standardized packaging on warning salience and effectiveness. That warning salience and effectiveness only increased in the UK postimplementation, where standardized packaging was implemented alongside new larger pictorial warnings on the pack front and reverse, and not in Norway, where standardized packaging was introduced but older smaller text warnings (pack front) and pictorial warnings (pack reverse) were retained, highlights the importance of removing full branding and introducing stronger warnings simultaneously.